Factors of Bank specific variables on Profitability: A CAMEL Framework - Prajapat, Swati; Ojha, Nupur (International Journal of Psychosocial Rehabilitation, 2020)
The profitability of the Indian banking sector has always remained a matter of concern amongst the policy makers and the bankers. In the contemporary phase of financial instability, banks are facing a lot of pressure and competition leading vulnerability to the system. Banks are required to prove their operational efficiency even more to earn higher profits which in turn stimulates the capacity of absorb risks. Moreover, efficient banking leads to greater financial stability of the economy and thus support economic growth. The study tries to explore the impact of variables specified in CAMEL framework on banks profitability. All scheduled commercial banks viz., public (state-owned) banks, private banks and foreign banks will be covered under this study. The secondary data of all the banks covered has been analyzed with the help of multiple regression model.